The relationship between intergrity and job performance among employees at Kementerian Perdagangan Dalam Negeri dan Hal Ehwal Pengguna (KPDNHEP), Putrajaya / Nurul Salwaliza Roslee - Roslee, Nurul Salwaliza (2019)
The title of this study is The Relationship between Integrity and Job Performance. The purpose of this research was to study the relationship between integrity (productivity, trust, work ethic) and job performance and also the most contributing variables influence job performance at Kementerian Perdagangan Dalam Negeri dan Hal Ehwal Pengguna (KPDNHEP), Putrajaya. Integrity allows us to measure on what is the most contributing variable that can influence in job performance in organization. The data were gathered through the questionnaires that were distributed to employees in Unit Integriti, Bahagian Akaun, Bahagian Pengurusan Sumber Manusia and Bahagian Khidmat Pengurusan dan Kewangan at KPDNHEP, Putrajaya. The population for this study is 181 respondents and the usable sample size is 124. The study found that there is a relationship between integrity (productivity, trust, work ethic) and job performance. The research questions will be answered to find out if there are findings indicated that there is positive, negative, strong and significant relationship or no relationship between productivity, trust and work ethic towards job performance among employees KPDNHEP, Putrajaya. There are numerous studies found that the productivity contribute more benefits on job performance but also some studies said that it can give bad impact